Wanprestasi dalam Hukum dan Transaksi jual beli rumah - Fadhil Arkan; Raja Syahnan Paparanta; Ridwandi Saputra; Helfira Citra (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2024)
This study undertakes a comprehensive examination of the legal aspects that govern agreements in house sales transactions. It specifically focuses on key issues such as the criteria for a valid contract, the legal ramifications of a breach, and the protections available for buyers. Employing a normative approach, the research analyzes relevant laws, regulations, court rulings, and pertinent legal literature. The findings indicate that house sale agreements possess unique characteristics that must be taken into account, highlighting the significance of written contracts in mitigating disputes. Furthermore, the study identifies several legal gaps that need to be addressed in order to enhance the protections afforded to all parties involved in house sales transactions.